Impact of Personalization and Consumer Trust on Purchase Intentions (Case Study of Social Media Marketing in the Fashion Industry) - Etty Zuliawati Zed; Sesri Sellina (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines how consumer trust and customization affect purchase intentions in the context of fashion industry social media marketing. 400 respondents who frequently interact with fashion businesses on social media platforms provided data for the study using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that customer trust and purchasing intentions are significantly enhanced by customisation. Furthermore, the relationship between personalization and purchase intentions is partially mediated by consumer trust, indicating that customized marketing tactics work better when trust is built. According to the R-squared values, personalization has a moderate to significant explanatory power, accounting for 27.3% of the variation in customer trust and 42.1% of the variation in buy intentions when combined with trust. These results demonstrate how important trust-building and tailored content are to increasing customer involvement and influencing purchase decisions in social media marketing. Fashion firms looking to improve their social media strategies will benefit greatly from the study's insightful findings, which highlight the need for openness, customer-centric customisation, and building trust to increase purchase intentions.